The efficacy and safety of Tisotumab vedotin in the treatment of recurrent/metastatic cervical cancer: a systematic review and meta-analysis of single-arm studies - Siyuan Zeng; Siyuan Zeng; Xin Li; Simin Xiao; Peina Yang; Peina Yang; Changsheng Lin; Changsheng Lin; Huiling Chen; Huiling Chen; Hu Zhao; Hu Zhao; et al. (Frontiers in Pharmacology)
ObjectiveThis study was conducted to evaluate the efficacy and safety of Tisotumab Vedotin (TV) in the treatment of recurrent/metastatic cervical cancer (r/m CC) through a systematic review and meta-analysis.MethodsThe clinical studies on the monotherapy of TV for r/m CC were retrieved comprehensively from some databases, including PubMed, Embase, and Cochrane Library. The inclusion criteria encompassed observational studies and randomized controlled trials. Data analysis was performed using STATA 15.0. Besides, the median overall survival (OS), median progression-free survival (PFS), disease control rate (DCR), objective response rate (ORR), and the incidence of adverse events (AEs) and AEs at Grades 3–5 were calculated.ResultsA total of 5 articles (covering 7 studies and 527 patients) were included in this study. The meta-analysis results revealed that the median OS, median PFS, ORR, and DCR were 11.83 months, 4.22 months, 29.9%, and 75.1%, respectively, for patients treated with TV. The incidence of AEs was 99.1%, and AEs at Grades 3–5 were reported in 61.7% of patients.ConclusionTV demonstrates significant efficacy as a second-line or third-line therapy for r/m CC, making it a promising therapeutic option. Nevertheless, large-scale randomized controlled trials are needed to validate these findings and optimize clinical application strategies.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024577046, identifier CRD42024577046.